2021
DOI: 10.1177/1071100721997070
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Deltoid Ligament Degradation in Patients With Chronic Ankle Instability Using Computed Tomographic Images

Abstract: Background: Rotational ankle instability (RAI) is associated with the faster onset of severe ankle osteoarthritis via dysfunction of the anterior talofibular ligament, calcaneofibular ligament, and deltoid ligament. No specific clinical examination is available for RAI, and diagnostic imaging has limitations in evaluating ligament degradation. This study investigated the deltoid ligament degeneration using Hounsfield unit (HU) values on computed tomography (CT) images. Methods: Patients were enrolled in this r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…37 Another cross-sectional imaging alternative is the computed tomographic scan, which has shown its usefulness in daily clinical practice. 6,28 Nevertheless, cross-sectional imaging by magnetic resonance imaging or computed tomographic scan does not allow dynamic investigation. Ultrasonography is a good alternative because it allows dynamic study of the ankle ligaments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…37 Another cross-sectional imaging alternative is the computed tomographic scan, which has shown its usefulness in daily clinical practice. 6,28 Nevertheless, cross-sectional imaging by magnetic resonance imaging or computed tomographic scan does not allow dynamic investigation. Ultrasonography is a good alternative because it allows dynamic study of the ankle ligaments.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty consecutive subjects (10 females, 10 males), all residents or medical students of the department, with a mean age of 22.2 years (range [22][23][24][25][26][27][28][29][30][31] were enrolled in the study between November 2020 and January 2021. A questionnaire was administered to ensure the absence of any medical history of fracture, sprain, or ankle surgery.…”
Section: Patientsmentioning
confidence: 99%
“…69 CAI and deltoid ligament injuries lead to a faster onset of OA. 37 Ankle OA usually occurs in younger productive-age individuals, progressing more rapidly to advanced stages and resulting in longer time with pain and loss of function. Clinical studies on the subject have shown that displacements of the talus of up to 1 mm with respect to the articular surface of the distal tibia can cause loss of tibiotalar contact of up to 42%.…”
Section: Associated Injuriesmentioning
confidence: 99%
“…12 Patients with chronic lateral ankle instability may develop rotatory ankle instability, secondary to a combination of lateral and medial lesions, usually after a long history of lateral ankle symptoms. [35][36][37] It is defined as an abnormal increase of talar rotation within the tibiofibular mortise due to ATFL deficiency, combined with CFL and deltoid ligament injuries. Secondary to chronic deficiency of the lateral ligaments, the talus goes into excessive internal rotation and anterior translation and increases the stress at the most anterior fascicles of the deltoid ligament, leading to rupture or detachment of the most anterior component of the deltoid ligaments, especially the superficial deltoid complex.…”
Section: Lesions and Patterns Of Injuriesmentioning
confidence: 99%
See 1 more Smart Citation